Life of David Lack : Father of Evolutionary Ecology. - Anderson, R. T. (R. Ted) (Oxford University Press, USA, 2013)
"Most people who have taken a biology course in the past 50 years are familiar with the work of David Lack, but few remember his name. Almost all general biology texts produced during that period have a figure showing the beak size differences among the finches of the Galapagos Islands from Lack's 1947 classic, Darwin's Finches. Lack's pioneering conclusions in Darwin's Finches mark the beginning of a new scientific discipline, evolutionary ecology. Tim Birkhead, in his acclaimed book, The Wisdom of Birds, calls Lack the 'hero of modern ornithology.' Who was this influential, yet relatively unknown man? The Life of David Lack, Father of Evolutionary Ecology provides an answer to that question based on Ted Anderson's personal interviews with colleagues, family members and former students as well as material in the extensive Lack Archive at Oxford University"--